El humor en la Comunicación Política - Valbuena de la Fuente, Felicísimo (CIC. Cuadernos de Información y Comunicación, 2010)
This article’s author attempts to uncover the factors that contributed to the international success of the series Yes, Minister and Yes, Prime Minister. To achieve this purpose, he uses various theories, believing that one can not explain all the factors. As a methodology, he applies content analysis, although with different nuances in each section. He also discusses the results and reaches conclusions that confirm the hypotheses formulated. Finally, he ridicules a recent definition of political communication and proposes to review the concepts used in a superficial way and that can only lead to the discredit of political communication.